2016
DOI: 10.1136/heartjnl-2015-308927
|View full text |Cite
|
Sign up to set email alerts
|

The associations of leptin, adiponectin and resistin with incident atrial fibrillation in women

Abstract: In women, elevated levels of serum resistin are significantly associated with higher rates of incident AF and partially mediate the association between BMI and AF. In the same population, leptin and adiponectin levels are not significantly associated with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
1
26
1
2
Order By: Relevance
“…Moreover, the renin–angiotensin system is activated in patients with low body weight, leading to advanced atrial fibrosis . Finally, adipokines such as leptin, adiponectin, and resistin, which are correlated with BMI, have been reported to be involved in the development of AF . As shown by Haynes et al, low body weight is associated with abnormal circulating adipokine levels, which may contribute to eating disorders and poor nutritional status .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the renin–angiotensin system is activated in patients with low body weight, leading to advanced atrial fibrosis . Finally, adipokines such as leptin, adiponectin, and resistin, which are correlated with BMI, have been reported to be involved in the development of AF . As shown by Haynes et al, low body weight is associated with abnormal circulating adipokine levels, which may contribute to eating disorders and poor nutritional status .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, Ermakov at al. revealed that in a group of postmenopausal women (50-79 years-old), during over 11 years of observation, serum resistin levels were independently associated with new AF onset [13]. The authors concluded that resistin may be considered as a biomarker that partially mediates the relationship between obesity and AF.…”
Section: Baseline Adipokine Levels and Future Atrial Fibrillation Devmentioning
confidence: 97%
“…Over a follow-up of 11.1 years, 18% of 4937 women developed AF 5. In multivariable analysis, adiponectin and leptin were not found to predict incident AF in their cohort.…”
mentioning
confidence: 92%